The Higher the Children's Achievements, the Better the Elderly Health? Evidence From China - Zhang, Pei ru; Liu, Yiwei (Frontiers in Public Health, 2022)
Health, an important indicator for measuring the elderly's life and wellbeing, is an important part of positive and healthy aging. Children's achievements are closely linked to their parents' health. However, existing literature does not cover how children's achievements impact the health of their elderly parents. Data were derived from the 2014 Chinese Longitudinal Aging Social Survey; this study includes 6,793 elderly people ages 60 and older as samples. A multiple linear regression model was used to analyze the correlation between children's achievements and their elderly parents' health statuses in China. The results show that the higher the children's income and education, the better their health of their elderly parents. Living patterns, children' financial support to their parents, and social capital play a mediating role in the relationship between children and their elderly parents. These findings provide further insight into potential factors associated with the children's achievements and elderly health.